Integrasi Nilai-nilai Pendidikan Islam dalam Industri Halal: Perspektif Etika, Sains, Ekonomi, dan Politik untuk Pembangunan Berkelanjutan - Nuryanti (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
The halal industry has experienced rapid global growth, but its challenges extend beyond economic aspects. This research examines the roles of ethics, science, economics, and politics in supporting the sustainability of this sector. Using a qualitative approach, the study's findings indicate that optimizing the potential of the halal industry requires synergy between ethical values, scientific innovation, economic strength, and supportive political policies. The ethical dimension ensures fair and sustainable practices, science drives technological advancements for efficiency and transparency, economics fosters market growth, and politics provides clear regulations. The synergy between these dimensions will strengthen the halal industry's position internationally, promote sustainable development, and address challenges such as limited ethical understanding, technology access, and inconsistent regulations